Deixis Analysis on the Ellen Show YouTube Channel - Mashfiyah, Ovi Sayidah; Sapari, Gigin Ginanjar; Nurmala, Ela (Jurnal Bahasa Inggris Terapan, 2023)
Deixis refers to the study of language usage, whether spoken or written, in order to indicate or point to something specific. The objective of this research is to analyze the deixis employed in The Ellen Show's YouTube channel and comprehend the meaning conveyed through this deixis. The study utilized a qualitative approach with content analysis. The analysis was conducted by applying deixis theory proposed by Yule. The findings reveal three categories of deixis found in the data: person deixis, spatial deixis, and temporal deixis. Among these, temporal deixis is the most prevalent, followed by person deixis, and spatial deixis is the least frequently used. In addition, the analysis of the data shows that person deixis is used to clarify by whom a sentence was uttered and to whom it refers. Spatial deixis is used to clarify a sentence regarding the place and reference of a word. Meanwhile, temporal deixis is used to give a description of the time and description of an event occur. To conclude, the use of deixis in communication may convey clear information about who is talking, where it takes pace, and when it happens.